SUSTAINABLE CHEMISTRY ORIENTED ON CHEMISTRY LEARNING TO INCREASE STUDENT AWARENESS TO THE ENVIRONMENT - Perkasa, Magfirah; Agrippina, Agrippina; Wiraningtyas, Wiraningtyas (Sainsmat : Jurnal Ilmiah Ilmu Pengetahuan Alam, 2017)
The development of science, technology and art influence on economic and social development of society. The rapid economic growth in Indonesia is still a profit-oriented bussines. The attitude of caring and awareness about the environment tend to be ignored by the employers even do not inserted and properly evaluated in the education curriculum in Indonesia. Attitudes towards environmental awareness needs to be instilled as early as possible to the students and evaluated particularly well in chemistry learning where has direct contact with the environment. The concept of sustainable development issued by the United Nations (UN) could be one of the solution to develop economic with environmental way and can be inserted into chemistry learning process. Sustainable development concept has three main domains are environmental, economic and social. There are several models and strategies of learning where has sustainable development orientation, are: experiental learning, project-based learning, values and character-based learning, inquiry learning, and others. The indicators of the students who have environmental awareness, are: 1) to know and be aware of issues and environmental issues, 2) have a perception and awareness of the issues and problems of the environment, and 3) have confidence in solving environmental problems and contribute to environmental improvement. Writing this article aims to outline the concept of sustainable development in learning chemistry so that it can be a reference for improving students' environmental awareness. This article will examine several issues, are: the concept of sustainable development, learning chemistry for sustainable development, sustainable development-oriented learning models and indicators of environmental awareness. Through this article, educators and stake holders are expected to be able to insert and apply the concept of sustainable development in the learning process chemistry to enhance students' environmental awareness.